2020
DOI: 10.1021/acs.nanolett.0c01196
|View full text |Cite
|
Sign up to set email alerts
|

The Density of Surface Coating Can Contribute to Different Antibacterial Activities of Gold Nanoparticles

Abstract: With the widespread use of antibiotics, the number of complex infection cases caused by unknown pathogens is increasing and novel antibiotics with tunable antibacterial spectra and low toxicity are highly desirable. Herein, we report that, by selecting thiol or amine, two groups with different binding affinities with gold, as anchoring groups, phenylboronic acid can be decorated on gold nanoparticles (AuNPs) with different densities, which contributes to Gram-selective antibacterial activities of the AuNPs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 30 publications
0
76
0
1
Order By: Relevance
“…For instance, silver nanoparticles (AgNPs) have been widely used as potent antimicrobials against bacteria because of their remarkable bactericidal effect exceeding that of other metal oxides and reduced possibility of inducing resistance. Gold nanoparticles (AuNPs) are another type of inorganic nanoparticles that widely tested as antimicrobial agent because of their photothermal activity, biocompatibility, and easy modification with small antimicrobial drugs [65,[66][67][68]. Furthermore, there is a particular interest in biosynthesized nanoparticles, such as copper nanoparticles prepared with Zingiber officinale, and Curcuma longa that displayed a remarkable antibacterial activity against multidrug resistant Staphylococcus aeureus [68].…”
Section: Nanoparticles Act As Antibacterial Materialsmentioning
confidence: 99%
“…For instance, silver nanoparticles (AgNPs) have been widely used as potent antimicrobials against bacteria because of their remarkable bactericidal effect exceeding that of other metal oxides and reduced possibility of inducing resistance. Gold nanoparticles (AuNPs) are another type of inorganic nanoparticles that widely tested as antimicrobial agent because of their photothermal activity, biocompatibility, and easy modification with small antimicrobial drugs [65,[66][67][68]. Furthermore, there is a particular interest in biosynthesized nanoparticles, such as copper nanoparticles prepared with Zingiber officinale, and Curcuma longa that displayed a remarkable antibacterial activity against multidrug resistant Staphylococcus aeureus [68].…”
Section: Nanoparticles Act As Antibacterial Materialsmentioning
confidence: 99%
“…We also compare the inhibition effects of MAAs and ampicillin, Oxacillin and vancomycin by testing the optical density at 600 nm (OD600) of bacterial suspensions by microplate readers (Tecan infinite M200), and recording the turbidities of bacterial suspensions by Nikon D90 camera. 36 Time-dependent killing assay. We incubate MRSA (≈10 6 CFU/mL) with different concentration of MAAs (0.5, 1 and 2 g/mL), oxacillin (32 μg/mL) and vancomycin (32 μg/mL) in LB medium for 4, 8, 12, and 24 h. 23,37,38 The suspensions are diluted for 10, 1000, and 100000 folds, and 100 L of the dilutions are placed on LB plates and incubated at 37  C for 24 h. Colonies are counted and CFU/ml is calculated.…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…Wang et al reported that two groups with different binding affinity to gold were used as anchor groups, and thiols or amines were used to modify phenylboronic acid on gold nanoparticles (AuNPs) with different densities. Different bacteria will have selective antibacterial properties, which are expected to be used for personalized treatment [67]. Gold nanoclusters conjugated with various surface ligands have high biocompatibility, multivalent effects, easy modification, and photothermal stability, so they are potential antibacterial agents.…”
Section: Antibacterial Effects Of Photothermalmentioning
confidence: 99%